Effect of coronary artery bypass surgery on ventricular functions in patients with poor left ventricular function - Öztürk, Cüneyd; Yavuz, Şenol (The European Research Journal, 2019)
Objectives: The aim of the present study was to compare preoperative / postoperative ventricular functions of patients with ventricular dysfunction who were planned for coronary artery bypass grafting (CABG) using echocardiography and angiography, and to evaluate whether there was a significant improvement in ventricular function. Methods: This prospective study included 30 patients with poor ventricular function who had undergone CABG at the Cardiovascular Surgery Clinics of Bursa Yüksek Ihtisas Hospital. The patients’ ventricular functions were compared preoperatively and postoperatively at the 2nd, 6th and 12th months. Results: Of the patients, 28 were males, and the mean age was 60.1 ± 8 years (range 39-71). In these cases, functional capacity improved within the early postoperative period, and global ventricular functions improved within the postoperative first year. The improvement in ejection fraction results was statistically significant at 6 months and 12 months (p < 0.05). A significant decrease was observed in left ventricular enddiastolic pressures within one year (p < 0.001). For the performance score, improvement was significant from the 2nd month (p < 0.05). Conclusions: Our findings show that CABG improves ventricular function in terms of EF, PS, LVEDP and NYHA classification. In conclusion, we consider that CABG is a significantly effective option in patients with poor ventricular function.